Transponder and Reader Concept for a HF Locating System - Schäfer, Tobias; Vossiek, Martin (6th German Microwave Conference (GeMiC) 2011, 2011)
This paper presents a low-frequency local positioning system operating at 13.56 MHz. With a wavelength of around 22 m the system operates in the near field. The phase shift between a CW signal generated at the base station and the response generated in a transponder is measured. The transponder is using the novel switched injection locked oscillator concept (SILO). Measurement results show that the proposed concept allows for robust indoor ranging with an uncertainty in the decimeter-range. The system is aiming at short range indoor localization problems, where a measurement through a crowd of people is required. Indoor navigation or information systems e.g. in museums, public buildings or fairs are possible applications.
lhft_intern.bib::Schaefer2011